2013
DOI: 10.1039/c3ta12303k
|View full text |Cite
|
Sign up to set email alerts
|

Silicon alkoxide cross-linked silica nanoparticle gels for encapsulation of bacterial biocatalysts

Abstract: A method is developed for encapsulation of bacterial biocatalysts in silica gels formed by silica nanoparticles (SNP) and a silicon alkoxide crosslinker. Formulation of the gel was optimized by changing the SNP size, SNP to crosslinker ratio and crosslinker functionality. Hydrolysis and condensation reactions of silicon alkoxide were controlled by water to alkoxide ratio (r) and pH of the solution. FTIR analysis verified that a reactive and temporally stable silicon alkoxide crosslinker was obtained. As a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…The ω = 0.11 gel microstructure was distinctly different with alkoxide aggregates gluing clusters of loosely packed SNPs together. The conclusions of the microstructural analysis was consistent with what was reported previously in similar gels (Mutlu et al, ; Perullini et al, ) and supported the mechanical testing results.…”
Section: Resultssupporting
confidence: 91%
“…The ω = 0.11 gel microstructure was distinctly different with alkoxide aggregates gluing clusters of loosely packed SNPs together. The conclusions of the microstructural analysis was consistent with what was reported previously in similar gels (Mutlu et al, ; Perullini et al, ) and supported the mechanical testing results.…”
Section: Resultssupporting
confidence: 91%
“…This increase was attenuated when using cells encapsulated into silica gels (Fig. 2B), due to the diffusion limitation imposed by the silica gel matrix (13,18). This limitation also causes an order-of-magnitude difference between the activity rates of suspended and encapsulated cells (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were encapsulated as hemispherical silica beads (1.0 to 1.5 mm in diameter) in molds as previously described (18). A 6.6-g quantity of the beads was placed in the bioreactors.…”
mentioning
confidence: 99%
“…Noticeably, previous reports on silicate:Ludox hydrogels showed that, at a fixed total silica concentration (2.1 M), the Young's modulus slightly decreases as the relative amount of Ludox increases, which was correlated with the increase in the porous volume. 23 The mechanical properties of tetraethoxysilane:Ludox (HS-40) silica hydrogels were also reported, 58 showing that the mechanical stability of the gel increased with increasing alkoxide content at constant particle concentration. Using larger particles, for a given total silica concentration, the elastic modulus of the gel decreased with increasing particle size.…”
Section: 61mentioning
confidence: 99%
“…However, it was observed that small variations in the protocol could have a large impact on the hydrogel structure and therefore on its chemical and mechanical stability, as well as on its optical properties. 30 While successful results have been recently obtained by substituting silicates with silicon alkoxides, 31 most research in this area turned towards the design of (nano)biocomposite hosts, in which biological molecules such as phospholipids 32,33 or polysaccharides 34,35 were used not only to provide a more cytocompatible environment to the cells but also as the template to control the internal structure and morphology of the hosts. Nanocomposites associating silica nanoparticles with organic polymers with promising mechanical properties were also described but their use for cell encapsulation was not reported so far.…”
Section: Introductionmentioning
confidence: 99%